Treatment outcome in tuberculosis patients under DOTS treatment, tuberculosis unit, Nahan, Himachal Pradesh, 2013-2015: a record based descriptive study - Kashyap, Rashmi; Singh, Kamaljit (International Journal Of Community Medicine And Public Health, 2018)
Background: Tuberculosis (TB) has existed for millennia and remains a major global health problem. There has been significant progress in cure rates achieved in revised national tuberculosis programme (RNTCP), however concerns regarding effectiveness of RNTCP regimens, still exist. These concerns could be addressed through an assessment of treatment outcome. The present study was conducted to ascertain the treatment outcome in tuberculosis patients under DOTS treatment. Methods: A record based descriptive study was conducted in patients enrolled under directly observed treatment strategy (DOTS). The data included the summary of case findings as new smear positive, new smear negative, new extrapulmonary, new others, relapse, failure, treatment after default, category II. Treatment outcome was assessed as cured, treatment completed, died, loss to follow up, failure and transferred out. Different variables were represented as frequency distribution and percentages. Chi square test was used to observe the association of different variables with the outcome of the disease. Results: A total of 899 patients were enrolled under DOTs treatment for tuberculosis. Sputum positivity was present in 481 (72.8%) patients. Outcome showed 384 (79.8%) patients as cured, treatment completed in 414 (81.8%) patients and treatment success rate of 798 (89.7%). Treatment failure was observed 9 (1.9%) patients. Conclusions: Treatment success rate of TB patients in this study was encouraging for TB control through DOTS strategy. However, to reduce poor treatment outcome, patients should be strictly followed by health workers or ASHAs.